(untitled) (Journal of Tropical Pharmacy and Chemistry, 2025)
This study aimed to ascertain clinical observations about the ability of the water extract of fresh garlic bulbs dayak eliminate lumps in the uterus (cysts) ovarian and ensure the necessary time or duration of administration of the extract to remove the lump or cyst woman’s uterus. The activities are making herbal tea preparation of fresh garlic bulbs dayak. Doses used in herbal teas of 8.4 grams / day. Each participant consumed herbal tea 2 times a day for 7 days continued to consume for 14 days. Then do an ultrasound to see the size of ovarian cysts before consuming or after consuming a herbal tea. The results of the study of fresh garlic bulbs clinical observations show that the herbal tea dayak give change ovarian cyst size of each respondent. Use of herbal tea in the observation of this study was 4.2 grams with the rules of drinking 2 times daily (8.4 grams / day) and change the size of ovarian cysts are consumed during the 7 days and continued for 14 days.